Analysis of received signal strength in indoor environment of telecommunication system - Myint Myint Mon; Mya Mya Aye; Lei Lei Yin Win (Journal of Computer-based Instructional Media, 2026)
To improve the performance of wireless communications in indoor environment, it is important to optimize the signal quality by reducing the error rate between the received signal strength based on experimental data and estimating data. Due to the complexity of modern building layouts and construction materials, estimating signal strength values based on these structural elements is challenging. The aim of this paper is to analyse received signal strength of the specific area by using the path loss exponent model of ray tracing techniques. In indoor environments, modelling radio wave propagation involves estimating the received signal strength at various points based on the layout and geometry of the space. This study involved three placements of 1.8 GHz AAU5940 Wall Mounted transmitters at height with 11.12 m and at different distances with 44.81 m, 95.4 m, and 108.2 m of specific receiver building. The Received Signal Strength Indicator (RSSI) readings are typically recorded to analyse and understand the ray tracing technique characteristics in a wireless communication environment. This paper presents analytical results of some practical experiments that help to build an optimized signal quality for indoor environment using mathematical modelling with the help of MATLAB software.